Correlation between primary chemical structure and property phenomena in polycondensates: dedicated to Professor K.-H. Büchel on the occasion of his 60th birthday - Sommer, Klaus; Heermann, Dieter W.; Kremer, Kurt (Advanced materials, 1991)
Polycondensates (polycarbonates (PC), polyetherketones (PEK), and polyethersulfones (PES) in the present context) have an important share of the market for engineering and high-performance thermoplastics. A knowledge of the relationships between the chemical structures of monomers and the properties of the polymers is an important prerequisite for the development of new plastics and the improvement of existing ones. These relationships can be investigated through the characterization of systematically varied polycondensate structures, and by the application of theoretical simulation methods developed to provide a better understanding of the propertydetermining structural elements and for the prediction of polymer characteristics. This article presents results relating to structure-property correlations (including various experimental results), static simulations of the amorphous polymer solid (“amorphous cell”) type, and dynamic Monte Carlo lattice simulations using the bond fluctuation algorithm.
Gesehen am 23.08.2017